2014
DOI: 10.1021/mz400650q
|View full text |Cite
|
Sign up to set email alerts
|

Protonation-Induced Microphase Separation in Thin Films of a Polyelectrolyte-Hydrophilic Diblock Copolymer

Abstract: Block copolymers composed of poly(oligo ethylene glycol methyl ether methacrylate) and poly(2-vinylpyridine) are disordered in the neat state but can be induced to order by protonation of the P2VP block, demonstrating a tunable and responsive method for triggering assembly in thin films. Comparison of protonation with the addition of salts shows that microphase separation is due to selective protonation of the P2VP block. Increasing acid incorporation and increasing 2-vinylpyridine content for P2VP minority co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…LS‐SCFT can provide a map of how the phase diagram can be changed as the block is charged, shown in Figure b . This effect is extremely pronounced, and follows the same general trends that polymer blends show . Interestingly, the morphologies are altered along with the order‐disorder transition temperature .…”
Section: Modern Approaches To Charge Correlationsmentioning
confidence: 73%
See 1 more Smart Citation
“…LS‐SCFT can provide a map of how the phase diagram can be changed as the block is charged, shown in Figure b . This effect is extremely pronounced, and follows the same general trends that polymer blends show . Interestingly, the morphologies are altered along with the order‐disorder transition temperature .…”
Section: Modern Approaches To Charge Correlationsmentioning
confidence: 73%
“…One possibility is to use simulation to understand structure, however, computation time can become a challenge when systems possess structure at length scales orders of magnitudes larger than the RPM charge. For example, block copolymers, liquid crystals, polymer brushes, and blends are all systems of interest to the polymer community that can include charge and possess large length scale structure. Furthermore, extension of correlation ideas to complicated biological systems is even more difficult using phenomenological models.…”
Section: Modern Approaches To Charge Correlationsmentioning
confidence: 99%
“…For this reason, an acid containing a weakly coordinating anion (tetrafluoroborate) commonly used in ionic liquids was used to protonate the pyridine rings. While protonation with tetrafluoroboric acid did raise the glass temperature of P2VP, the amount by which it did so was moderate (there was only a 77 °C increase between unprotonated and 80% protonated P2VP; see the Supporting Information), as compared to hydrochloric and hydriodic acid . This provided sufficient mobility for morphological changes with temperature to be observed in many cases.…”
Section: Methodsmentioning
confidence: 98%
“…Testing these predictions has proven challenging because it is difficult to find charge asymmetric block copolymers that are close to their ODT, and because many polyelectrolytes have a very high glass temperature in the absence of a solvent. In previous work, we have shown that poly(oligoethylene glycol methyl ether methacrylate)‐poly(2‐vinylpyridine) (POEGMA‐P2VP) block copolymers have a protonation‐induced order–disorder transition, making them ideal materials to test the phase behavior of charge‐asymmetric block copolymer systems . These materials are fully water‐compatible so that solvent annealing in aqueous vapors is possible, which facilitates equilibration.…”
Section: Introductionmentioning
confidence: 99%
“…Building on this foundational research, coacervates have found utility as encapsulants, additives, emulsifiers, and viscosity modifiers in food science and personal care products . The scope of coacervation has expanded from proteins and polysaccharides to include polynucleotides, synthetic polymers, surfactants, nanoparticles, and other hierarchical assemblies . Furthermore, the utility of coacervates has extended into fields such as adhesives, drug delivery, nano/bioreactors, and cellular biology …”
Section: Introductionmentioning
confidence: 99%